RNA interference and cancer: a revolution? - Harel-Bellan, Annick (Henry Stewart Talks, 2007)
Cancer overview, RNA interference to understand cancer, Natural short RNAs in cancer, RNA interference to fight cancer
Reviewed at 2016/10/13